Hydrophilic Nasal Gel of Lidocaine Hydrochloride - Hu, Kai-Li; Mei, Ni; Feng, Liang; Jiang, Xin-Guo (Arzneimittelforschung, 2009)
Intranasal lidocaine hydrochloride (LID, CAS 73-78-9) has been shown useful in the control of a series of symptoms such as migraine, cluster headache and trigeminal neuralgia in clinical studies. However, rapid nasal mucociliary clearance of intranasal solution usually affects its efficiency. In this study, a nasal gel formulation was designed using hydroxy-propyl methyl cellulose (HPMC) as mu-coadhesive polymer to increase the residence time of LID on the nasal mucosa. Based on the results of a preliminary single factor study, the gel formulation was optimized by central composite design to provide better drug release and bioadhe-sive intensity. The methods for investigating the gel’s bioadhesive intensity and for spectrophotometric determination of LID were established. Then the parameters for the LID in vitro release study such as release medium, release apparatus and rotation rate were decided upon a method of f2 fit factor. The in vitro drug release property of the optimized formulation was proved to comply with the Higuchi equation.
Keywords: CAS 73-78-9; Central composite design; Lidocaine hydrochloride; Local anesthetics; Mucoadhesive polymer; Nasal gel